Perspective: science and the future of livestock industries - Martin, Graeme B. (Frontiers in Veterinary Science, 2024)
Since the 1990s, livestock industries have been forced to respond to major pressures from society, particularly with respect to methane emissions and animal welfare. These challenges are exacerbated by the inevitability of global heating and the effects it will have on livestock productivity. The same challenges also led to questions about the value of animal-sourced foods for feeding the world. The industries and the research communities supporting them are meeting those challenges. For example, we can now envisage solutions to the ruminant methane problem and those solutions will also improve the efficiency of meat and milk production. Animal welfare is a complex mix of health, nutrition and management. With respect to health, the ‘One Health’ concept is offering better perspectives, and major diseases, such as helminth infection, compounded by resistance against medication, are being resolved through genetic selection. With respect to nutrition and stress, ‘fetal programming’ and the epigenetic mechanisms involved offer novel possibilities for improving productivity. Stress needs to be minimized, including stress caused by extreme weather events, and solutions are emerging through technology that reveals when animals are stressed, and through an understanding of the genes that control susceptibility to stress. Indeed, discoveries in the molecular biology of physiological processes will greatly accelerate genetic progress by contributing to genomic solutions. Overall, the global context is clear – animal-sourced food is an important contributor to the future of humanity, but the responses of livestock industries must involve local actions that are relevant to geographical and socio-economic constraints.